2006
DOI: 10.1093/ps/85.4.770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Egg Size on Heat Production and the Transition of Energy From Egg to Hatchling

Abstract: An experiment was conducted to study the effect of egg size on embryo development, heat production, and energy partitioning between egg and hatchling. Small (56.1 +/- 0.12 g SEM) and large (70.0 +/- 0.11 g SEM) hatching eggs were incubated in climate respiration chambers, and eggshell temperature was maintained constant at 37.8 degrees C in both egg weight classes by adjusting machine temperature. Dry matter, ash, protein, and fat contents were determined in albumen, yolk, yolk-free body (YFB), and residual yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 20 publications
2
56
0
12
Order By: Relevance
“…Deeming and Van Middelkoop (1999) reported that as the flock ages, there was more infertility and early embryonic mortality in eggs from Ross 308 compared with Cobb 500. It is well recognized that there is a strong relationship between breeder age and egg weight such that older hens produce larger eggs (Lourens et al 2006). Chick weight increased with advancing age of broilers' breeders as reported by Yildirim (2005) and Christensen et al (2002).…”
Section: Introductionmentioning
confidence: 79%
“…Deeming and Van Middelkoop (1999) reported that as the flock ages, there was more infertility and early embryonic mortality in eggs from Ross 308 compared with Cobb 500. It is well recognized that there is a strong relationship between breeder age and egg weight such that older hens produce larger eggs (Lourens et al 2006). Chick weight increased with advancing age of broilers' breeders as reported by Yildirim (2005) and Christensen et al (2002).…”
Section: Introductionmentioning
confidence: 79%
“…According to the literature, increased residual yolk is a sign of overheating (LEKSRISOMPONG et al, 2007), which reaffirms the possibility that non-scheduled variations at inadequate times may negatively affect normal development. In the industry, temperature variability in different regions of the machine is often observed (FRENCH, 2002), since there are eggs of various origins and in different phases of development, in addition to differences in metabolism, oxygen consumption, and size due to breeder hens of different ages (LOURENS et al, 2006;HAMIDU et al, 2007). This study evaluated the development of embryos from Ross ® breeder hens aged between 61 and 63 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Incubation occurred in two different climate respiration chambers (CRC), one for each treatment (Lourens et al, 2006). Egg shell temperature (EST) was used as treatment applied to the eggs, as a reflection of embryo temperature (Lourens, 2001).…”
Section: Methodsmentioning
confidence: 99%